1999
DOI: 10.1080/11250009909356261
|View full text |Cite
|
Sign up to set email alerts
|

A molecular cytogenetic comparison of planarians from the’Dugesia gonocephalagroup’ (Platyhelminthes, Tricladida)

Abstract: Zool., 66. 239-244 (1999) A molecular cytogenetic comparison of planarians from the 'Dugesia gonocephala group' (Platyhelminthes, Tricladida) RENATA BATISTONI LEONARDO ROSSI ALESSANDRA SALVETTI PAOLO DERI Laboratorio di Biologia Cellulare e dello Sviluppo, Dipartimento di Fisiologia e Biochimica, Università di Pisa, via Carducci 13, I-56010 Ghezzano, Pisa (Italy) ABSTRACT Planarians belonging to the Dugesia gonocephala group share extensive karyotype similarities when compared using classical cytological te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
(1 reference statement)
1
3
0
Order By: Relevance
“…Nevertheless, the populations from Calabria, Sicily and Morocco can be tentatively attributed to D. sicula, in that it possesses a basic haploid number n = 9 and presents a wide and disjunct distribution, which includes the areas where these populations have been collected. Also recent molecular cytogenetic data support this possibility (Batistoni et al, 1995(Batistoni et al, , 1998.…”
Section: Discussionsupporting
confidence: 57%
“…Nevertheless, the populations from Calabria, Sicily and Morocco can be tentatively attributed to D. sicula, in that it possesses a basic haploid number n = 9 and presents a wide and disjunct distribution, which includes the areas where these populations have been collected. Also recent molecular cytogenetic data support this possibility (Batistoni et al, 1995(Batistoni et al, , 1998.…”
Section: Discussionsupporting
confidence: 57%
“…Some regions that are potentially suitable for D. sicula have not yet been widely sampled, such as northern Africa (except for Tunisia and some regions of Algeria and Morocco), the southwestern Iberian Peninsula and parts of the Italic Peninsula. However, restriction pattern analyses showed similarities among some populations north of the Italic Peninsula and D. sicula [ 59 , 60 ], although the Italian populations could not be identified; moreover, Benazzi and Deri [ 61 ] reported populations in Tuscany (including the island of Pianos), Ponza Island (between Rome and Naples), Rome (Lazio) and Calabria that could be attributed to D. sicula based on morphological features, and some populations with a chromosomal complement of 27+ 2B chromosomes have been reported in Calabria by Deri et al [ 62 ]. In other areas, D. sicula has never been reported (Corsica) or is relegated to the periphery (Sardinia), although these regions appear to fulfil the climatic requirements of the species.…”
Section: Discussionmentioning
confidence: 99%
“…A molecular cytogenetic comparison of several species and populations of the genus Dugesia revealed that these planarians from Pogradec besides two telomeric NOR loci , also have a ribosomal site located in an intercalated position on the long arm of one of the largest chromosomes (Batistoni et al 1999). This peculiar condition differs from other planarian taxa, in which 18S + 28S rRNA genes appeared preferentially located on telomeric regions of medium-sized chromosomes, and was interpreted by the authors as a structural chromosomal rearrangement, such as a paracentric inversion, suggesting a case of speciation.…”
Section: Resultsmentioning
confidence: 99%